2018
DOI: 10.2478/ffp-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Activity of spore-crystal mixtures of new Bacillus thuringiensis strains against Dendrolimus pini (Lepidoptera: Lasiocampidae) and Spodoptera exigua (Lepidoptera: Noctuidae)

Abstract: We estimated the usefulness of spore-crystals preparations of the two B. thuringiensis isolates, MPU B9 and MPU B54, for reducing the number of pests. The potential insecticidal toxicities of B. thuringiensis isolates were assessed by the analysis of the genes coding for crystalline proteins. The activities of spore-crystals preparations were determined against Dendrolimus pini L. (Lepidoptera: Lasiocampidae) and compared with the toxicity of spores and crystals of B. thuringiensis subsp. kurstaki HD-1 from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Pest management of D. kikuchii mostly involves routine technologies, for instance, manual, physical, chemical, and biocontrol methods as well as forestry management. Biocontrol of the genus Dendrolimus with organisms such as Trichogramma dendrolimi, Beauveria bassiana, and Bacillus thuringiensis is safe, environmentally friendly, and effective long-term (Hou, 1987;Hou, 1993;Kunimi, 2007;Konecka et al, 2019). However, despite the broad prospect of utilizing pathogens in the biocontrol of D. kikuchii, the molecular mechanisms of interaction between D. kikuchii and such pathogens are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Pest management of D. kikuchii mostly involves routine technologies, for instance, manual, physical, chemical, and biocontrol methods as well as forestry management. Biocontrol of the genus Dendrolimus with organisms such as Trichogramma dendrolimi, Beauveria bassiana, and Bacillus thuringiensis is safe, environmentally friendly, and effective long-term (Hou, 1987;Hou, 1993;Kunimi, 2007;Konecka et al, 2019). However, despite the broad prospect of utilizing pathogens in the biocontrol of D. kikuchii, the molecular mechanisms of interaction between D. kikuchii and such pathogens are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…4 Programa de Pós-Graduação em Zootecnia (PPGZO), UTFPR-DV, Dois Vizinhos, Paraná CEP 85.660-000, Brazil. * email: profmichele@gmail.com biological control agents, the bacterium Bacillus thuringiensis (Bt), is considered successful 18 and efficient and is recommended for the control of insects, including those of Lepidoptera, Coleoptera, and Hymenoptera [19][20][21][22][23] . In general, the side effects of a biological agent vary for different organisms, owing to the greater specificity for the target organism.…”
Section: Openmentioning
confidence: 99%
“…B. thuringiensis MPU B9 was isolated from the intestinal tract of dead caterpillar of codling moth Cydia pomonella during epizootics caused by naturally occurred bacterial infection in the laboratory-cultured line of the insect (Konecka et al 2007a). B. thuringiensis MPU B54 was cultured from soil sample (Konecka et al 2018c).…”
Section: Bacteriamentioning
confidence: 99%
“…Moreover, mass spectrometry analysis revealed that MPU B9 crystals contained Cry1Aa, 1Ba, 1Ca, 1D, and 9E toxins (Baranek et al 2017). Bacterial crystals alone or with spores showed high insecticidal activity against insect pests (Konecka et al 2018c(Konecka et al , 2015(Konecka et al , 2012(Konecka et al , 2007b. B. thuringiensis strain MPU B54 harbored the following genes: cry1Aa, cry1Ab, cry1C, cry1D, cry1I, cry2Ab, cry9B, and cry9E.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation